Real-time fluctuations in student emotions and relations with day of the week, time of the day, and teaching methods - Camerman, Eline; Kuppens, Peter; Lavrijsen, Jeroen; Verschueren, Karine (Frontiers in Education, 2024)
IntroductionThis study investigated the real-time variability of secondary school students’ academic emotions (i.e., enjoyment, enthusiasm, boredom, and frustration) in mathematics classes, examining their relation to the day of the week, time of the day, and teaching methods. Utilizing experience sampling methodology, the research captures the dynamic nature of emotions as states, providing insights into their situational dynamics.Methods440 students reported twice during their mathematics classes for a period of 10 school days on their real-time experiences of academic enjoyment, enthusiasm, boredom, and frustration. Additionally, their teachers indicated the teaching methods that were used on each measurement occasion.ResultsResults indicated students to have a more positive emotional pattern on Fridays (i.e., a “Thank God it’s Friday” effect) and Wednesdays, likely due to the anticipation of leisure time. Additionally, a “Frustrating Tuesday” effect was observed, while no evidence was found for a “Blue Monday” effect. Time of the day effects were less consistent, with frustration increasing throughout the day and boredom being higher in the afternoon, possibly due to postprandial somnolence (i.e., post-meal dip). Teaching methods differently related to emotions; during individual and group work students experienced more enjoyment and enthusiasm but also more frustration compared to whole-class instruction. During classroom discussion more frustration was experienced relative to whole-class instruction. Female students experienced less enthusiasm than male students, and higher ability students experienced more enjoyment, enthusiasm and less boredom than lower ability students.DiscussionThis study underscores the importance of considering temporal factors and teaching methods in understanding students’ emotional experiences in educational settings.